PERAN INOVASI PRODUK MEMEDIASI ORIENTASI TEKNOLOGI TERHADAP KEUNGGULAN BERSAING - Widiarta, Putu Gde Kamasaka; Mahardika, I Putu Dicky; Nugraha, Nyoman Agus Surya; Tintara, I Dewa Gede Wilanta; Yasa, Ni Nyoman Kerti (E-Jurnal Ekonomi dan Bisnis Universitas Udayana, 2020)
This study discusses to explain the Role of Product Innovation Mediating Technology Orientation to Competitive Advantages. The sample used was 62 respondents obtained using non probability sampling method consisting of purposive sampling residing in the city of Denpasar, and having made transactions or used the services of Gojek. Data was collected using a full questionnaire and using a Likert scale. Data were analyzed using path analysis techniques and sobel tests. The results of this study prove that technological orientation is positive and significant towards the product innovation and competitive advantage. Product innovation are positive and significant to competitive advantage. Supported product innovation mediates an integrated orientation to competitive advantage. The implications of this research provide advice for Gojek Indonesia to support product improvement and pay attention to technological orientation related to the creation of superior competitiveness.